Influence of precipitation and runoff on human-induced land subsidence in the Yellow River Delta - Yaoshen Fan; Guangzhou Wang; Shentang Dou; Chao Jiang; Hongyu Ji; Shenliang Chen; Xiaokang Du; Shoubing Yu; Yan Wu; Shaohua Zhang (Quaternary Science Advances)
Land subsidence in river deltas, particularly in the Yellow River Delta (YRD), represents an urgent environmental concern driven by both human activities and natural factors. This study provides a comprehensive analysis of land subsidence in the YRD region from 2019 to 2022 using multi-temporal InSAR data from Sentinel-1A. Results reveal that the maximum annual subsidence rate in the YRD exceeds 200mm/a, with the primary subsidence area located in the northeastern part of the delta, forming a subsidence funnel of approximately 200 km2 and displaying distinct spatial heterogeneity. Human activities, especially saltwater extraction and oil exploitation, are the main drivers of land subsidence. Areas heavily influenced by human activities show significantly greater subsidence than well-protected ecological zones. The study reveals pronounced seasonal variations in land subsidence across the YRD, with subsidence rates in summer being substantially lower than those in spring, autumn, and winter. By introducing the concept of equivalent precipitation, the research confirms that runoff exerts a regulatory effect on land subsidence, although its impact is considerably weaker than that of precipitation. This study proposes a novel explanatory mechanism: the expansion-contraction properties of surface soil explain how seasonal hydrological conditions influence subsidence patterns. During rainy summers, surface soil absorbs water and expands, partially offsetting subsidence caused by deep extraction. These findings provide valuable insights into the interactions between human activities and natural factors in complex deltaic systems, offering a scientific basis for subsidence monitoring and sustainable resource management in the YRD region.